2022
DOI: 10.1111/jdv.18200
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer treatments and photosensitivity

Abstract: Drug‐induced photosensitivity is associated with a wide range of anticancer treatments, including conventional chemotherapeutic agents, targeted anticancer therapies, and immune checkpoint inhibitors. These dermatologic adverse events can have a major impact on the well‐being and quality of life of cancer patients, leading to dose modifications and interruption or discontinuation of anticancer treatments in severe cases. However, the heterogeneous nature of the photosensitive reactions induced by these agents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
(190 reference statements)
0
19
0
Order By: Relevance
“…Selective inflammation of AK during chemotherapy is possibly a consequence of direct cytotoxicity of an active compound on atypical keratinocytes that accumulate ultraviolet-induced damage of deoxyribonucleic acid, but the exact mechanism of how different chemotherapeutics achieve this effect seems to be drug-dependent [ 13 ]. Alternative explanations of skin lesions (i.e., subacute lupus erythematosus, actinic lichen planus, cutaneous vasculitis, hypersensitivity drug reactions, drug-induced photosensitivity reactions, and photocontact dermatitis) were in both patients excluded on the basis of a history, typical clinical features of AK, and in the first case with the additional characteristic presence of atypical keratinocytes on histological examination [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selective inflammation of AK during chemotherapy is possibly a consequence of direct cytotoxicity of an active compound on atypical keratinocytes that accumulate ultraviolet-induced damage of deoxyribonucleic acid, but the exact mechanism of how different chemotherapeutics achieve this effect seems to be drug-dependent [ 13 ]. Alternative explanations of skin lesions (i.e., subacute lupus erythematosus, actinic lichen planus, cutaneous vasculitis, hypersensitivity drug reactions, drug-induced photosensitivity reactions, and photocontact dermatitis) were in both patients excluded on the basis of a history, typical clinical features of AK, and in the first case with the additional characteristic presence of atypical keratinocytes on histological examination [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As immunotherapy for metastatic melanoma and other skin cancers is currently seeing great advancements, adverse effects, such as the development of photosensitivity, are becoming increasingly important. 5 A study of 634 patients, 38% of whom had high-risk (>2 mm) melanomas, revealed the influence that diet quality had on the development of this skin cancer. The Healthy Eating Index (HEI) was adopted to assess diet quality, and it was shown that melanoma patients who had good diets in the year preceding their diagnosis were less likely to have thick (>2 mm) melanomas than those who consumed a poorquality diet.…”
Section: Oncology a N D Ca Nce R Pr Ev E N Tionmentioning
confidence: 99%
“…As immunotherapy for metastatic melanoma and other skin cancers is currently seeing great advancements, adverse effects, such as the development of photosensitivity, are becoming increasingly important 5 …”
Section: Oncology and Cancer Preventionmentioning
confidence: 99%
“…9 However, the drawbacks of this hydrophilicity photosensitizer such as instability in blood circulation, low cellular uptake efffciency, and weak tumor-targeting capability greatly limit its application in anticancer strategies. 10,11 Currently, the biomimetic nanoparticle modification strategy has attracted more and more attention. Various extracted types of biomembranes coated on nanocarriers through special technology can endow nanoparticles with relative biological characteristics, thus exhibiting excellent anticancer efficacy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG) as an NIR fluorescent dye possesses both photosensitive and photothermal properties, which should sufficiently perform PTT and PDT effects in the treatment of OTSCC . However, the drawbacks of this hydrophilicity photosensitizer such as instability in blood circulation, low cellular uptake efffciency, and weak tumor-targeting capability greatly limit its application in anticancer strategies. , Currently, the biomimetic nanoparticle modification strategy has attracted more and more attention. Various extracted types of biomembranes coated on nanocarriers through special technology can endow nanoparticles with relative biological characteristics, thus exhibiting excellent anticancer efficacy. , Homologous tumor cells can exhibit self-recognition and agglomeration homing effects due to their similar proteins such as adhesion molecules expressed on the surface of cell membranes. Therefore, when encapsulated within the OTSCC cell membrane vesicles, the nanoparticles will be forecasted to achieve specific recognition and efficient cellular uptake by homologous OTSCC, thus hoping to overcome the limitations of ICG mentioned above.…”
Section: Introductionmentioning
confidence: 99%